Maternal deaths with epilepsy: A population-based study in Turkey. (March 2021) - Yucel, Aykan; Tanacan, Atakan; Atalay, Funda; Altinboga, Orhan; Koksal, Zuhal; Baydilli, Meltem Buz; Esen, Meral; Karabacak, Yurdum; Ongun, Veli Dundar; Sahlar, Tuba Esra; Keskinkilic, Bekir; Kara, Fatih
Abstract: Objective: To evaluate the clinical characteristics of maternal deaths with epilepsy in Turkey. Study design: This epidemiological population-based study was conducted on all consecutive early maternal deaths with epilepsy in Turkey from 2012 to 2019. Maternal deaths accompanied by epilepsy as a comorbidity (n = 13) were evaluated separately. Epilepsy related maternal deaths were divided into two groups: 1) status epilepticus (n = 19) and 2) Sudden unexpected death in epilepsy (n = 19). Two groups were compared in terms of demographic features and clinical characteristics. Results: Maternal deaths with epilepsy ranged between 2.5 % and 5.3 % among total maternal deaths. Pulmonary embolism (32 %), cerebrovascular event (23 %), and cerebral vein thrombosis (15.4 %) were the leading mortality reasons in maternal deaths accompanied by epilepsy. Epilepsy duration, the time interval between pregnancy and the last epileptic seizure, compatibility with medication, rates of preconceptional counseling, and regular antenatal follow-up were all significantly higher in the sudden unexpected death in epilepsy group. The perinatal complication rate was significantly higher in the status epilepticus group (p > 0.05). Conclusion: Physicians who deal with pregnant women with epilepsy should be attentive for severe complications and the increased risk of maternal mortality in these cases should be kept in mind.